Changes in the Gene Expression Pattern Induced by 2-Methoxyestradiol in the Mouse Uterus - Cardenas-Sankan, G; Orihuela-Diaz, P; Reuquen-Lopez, P; Diaz-Saldivar, P; Orostica, M (2012)
2-Methoxyestradiol (2ME) is an estrogen metabolite with antitumor and antiangiogenic properties, although their effects on the reproductive tissues are not well-determined. Furthermore, it is not very clear whether 2ME is part of the intracellular signaling of estradiol (E2) or it acts through other signaling pathways. The purpose of this study was to determine changes in the gene expression pattern in the mouse female reproductive tract induced by 2ME, under conditions in which this metabolite has no estrogenic activity. Therefore, we first compared the effect of 2ME or E2 on the uterine weight and epithelial cell height, and on the ovarian weight and the number of follicles of immature mice. Then, we examined the gene expression profile in the uterus of immature mice treated with 2ME or E2 and we selected three genes scd2, snx6, and spon1, to confirm differential regulation by E 2 and 2ME in the uterine cells using real-time PCR. Finally, in order to explore the physiologic relevance of the 2ME-induced genes we determined the expression and localization of the F-spondin protein encoded by spon1 in the uterus of mature mice treated with E2 or 2ME. Estradiol and 2ME reduced the ovarian weight and decreased the number of follicles ?300 ?m, whereas E2 increased the uterine weight and epithelial cell height but not 2ME, indicating that 2ME did not have estrogenic activity in the mouse uterus. Microarray analysis showed that 1.8 % of the uterine genes were regulated by E2 and 0.23 % by 2ME, while 0.04 % was regulated by E2 and 2ME. The mRNA for scd2 was exclusively increased by 2ME, whereas snx6 and spon1 were up-regulated by E2 and 2ME, but the response to 2ME was more intense. F-spondin was mainly expressed in the uterine stroma layer although 2ME or E2 did not change its localization in the uterine cells. We conclude that 2ME regulates a group of genes in the mice uterus, independently of estrogenic activity, suggesting a functional involvement of 2ME in the mammalian uterus. © 2013 Springer Science+Business Media New York.